Tomographic assessment of bone volume changes following regeneration with titanium Mesh in the maxillary anterior region. A retrospective clinical study - da ROCHA, Carolina Pinheiro; Zacharias, Ana Daisy; Marcantonio, Elcio [UNESP]; Kiatake Fontão, Flávia Noemy Gasparini; de MOLON, Rafael Scaf [UNESP]; de FREITAS, Rubens Moreno (My University, 2024)
Introduction: For a successful implant-supported rehabilitation and long-term maintenance in the anterior maxilla, it is imperative that the patient possesses adequate bone quality and quantity. Objective: The aim of this study was to assess bone gain and stability following reconstruction with titanium mesh in the anterior region of the maxilla, irrespective of the biomaterial used for bone augmentation. Material and method: Patient follow-up data were obtained from the Faculty's follow-up database. The focus was on individuals who had undergone rehabilitation in the anterior maxilla, previously augmented with bone grafts and growth factors in conjunction with titanium mesh. This retrospective cohort study involved at least 10 patients who met the inclusion criteria. Following an initial review of medical records, the eligible patients were invited for evaluation appointments. Result: Out of 39 patients who had undergone guided bone regeneration surgery using titanium mesh, 12 met the inclusion criteria. As such, 17 sites suitable for the study were obtained, from which total of 276 tomographic measurements were then taken. There was a noticeable increase in thickness at all assessment levels relative to the bone crest apex, both immediately (T1) and six months post-surgery (T2), compared to baseline measurements (T0). Moreover, bone thickness tended to increase with the proximity to the apical level. Conclusion: The use of titanium mesh combined with various biomaterials has yielded favorable outcomes in terms of augmenting bone volume.
Avaliação tomográfica das alterações ósseas volumétricas após regeneração com malha de titânio na região anterior da maxila. Estudo clínico retrospectivo
Keywords: biocompatible materials; Bone regeneration; dental implants